(untitled) (Konferensiyalar | Conferences, 2024)
The purpose of this study is to determine the differences between the historical and modern education systems. The comparison method was mainly used to determine the differences. It discusses how history education can limit students’ critical thinking and creativity. The historical education system usually includes a teacher-centered approach, where students receive education passively through lectures, textbooks, and exams. As you read the research, you can clearly see this in the “Gurukul” teaching system, which is one of the historical educational systems. However, in recent years, student-centered learning has supplanted the historical education system and there has been a shift to a more modern education system that emphasizes the use of technology to enhance the learning experience. Overall, the research provides insight into the benefits of transitioning from an older education system to an approach that better prepares students for the challenges of 21st century life.